CERITA RAKYAT JAKA BANDUNG: ANALISIS STRUKTURAL LEVI-STRAUSS - Handayani, Pipit Mugi Handayani (SASINDO, 2013)
Through folktales, people can express their mindset they had during the period of the tale. Folktales usually have myths that accompany the story. In this research, a folktale that will be discussed is a tale called âJaka Bandungâ, a story that comes from Prambanan area, Central Java and has been published. This folktale is one of the versions of the oral tales spread and grew in central java that used Levi-Straussâ structuralism analysis. The steps in the research is done by finding the mytheme and arrange the mytheme sintagmatically and paradigmatically. Â  Keywords: folktales, myth, mytheme, pattern